Pengaruh Privasi Dan Kepercayaan Terhadap Internet Pada Perilaku Pembelian Online - , Yusuf Nanda Pratama, Dr. Iin Mayasari, S.Pd, S.IP, MM, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to understand the impact of privacy and internet trust, on transaction online behavior. The Theory of Planned Behavior was applied for the theoretical foundation of the research. Hypotheses that are proposed: (1) internet trustworthy positively influences attitudes toward online purchasing